Lipopolysaccharide induces a stromal–epithelial signalling axis in a rat model of chronic periodontitis. (21st November 2012) - Firth, James D.; Ekuni, Daisuke; Irie, Koichiro; Tomofuji, Takaaki; Morita, Manabu; Putnins, Edward E.
Abstract Aim Lipopolysaccharide is a bacterial virulence factor implicated in chronic periodontitis, which may penetrate the junctional epithelial barrier and basement membrane to insult underlying stroma. We sought to identify lipopolysaccharide‐induced global gene expression changes responsible for signalling between stroma and epithelium during disease onset. Materials and Methods Using a rat lipopolysaccharide periodontitis model, junctional epithelium and underlying stromal tissue were separately collected from healthy and diseased animals by laser‐capture microdissection and subject to gene expression microarray analysis. Key gene products identified were validated in gingival epithelial and fibroblast cell cultures. Results Global gene expression patterns distinguishing health versus disease were found in and between both tissue types. In stroma, the most significantly altered gene ontology function group (Z ≥ 4.00) was cytokines, containing most significantly (±2‐fold; p < 0.05) upregulated genes amphiregulin, IL1‐β and Fas ligand, all positive, diffusible modulators of the epithelial growth factor receptor pathway. In epithelium, the most significant changes were in downregulated FOS‐related antigen‐1 gene, somatostatin receptor‐2 gene and mucin‐4 gene, all negative modulators of the epithelial growth factor receptor pathway. Conclusion These results establish a periodontitis model for studying gene product interactions and suggests that the onset of junctional epithelial disease hyperproliferation involves a concerted stromal–epithelial signalling axis.